Design and Optimization of High-Voltage MOSFETs - Wang, Chuanjie (Transactions on Computer Science and Intelligent Systems Research, 2024)
Silicon carbide (SiC) power devices have gained significant attention due to their broad applications in high voltage, high frequency, and high temperature environments. Traditional silicon (Si) power devices, although well-established, face performance limitations that SiC devices can overcome. High-voltage 4H-SiC MOSFET (Metal-Oxide-Semiconductor Field-Effect Transistor) devices are essential for the advancement of power electronics, and this work focuses on their design and optimization. First, a brief summary of the state of research on high-voltage 4H-SiC MOSFET devices is given, highlighting advancements and ongoing efforts in this field. Finally, the study delves into the design optimization of 4H-SiC MOSFET devices at high voltages, describing the vital design parameters and innovative techniques such as multi-zone modulation field limiting ring technology. The findings from this research provide valuable insights and practical guidance to improve SiC MOSFET devices' reliability and effectiveness, building upon the discussed design parameters and innovative techniques. This study significantly contributes to the manufacturing and utilization of electrical devices, promoting more efficient and reliable power conversion solutions in various high-demand sectors.